2017
DOI: 10.1093/intqhc/mzx129
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with malnutrition among children <5 years old in Burkina Faso: evidence from the Demographic and Health Surveys IV 2010

Abstract: In addition to the improvement of household wealth index, more health and nutritional education for mothers should be implemented by the government to improve health and nutritional status of children <5 years in Burkina Faso.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

66
89
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(159 citation statements)
references
References 27 publications
66
89
2
2
Order By: Relevance
“…This study found that age of the child significantly affected the child's nutritional status. This finding is consistent with findings from studies in Ethiopia and Bangladesh [23,26,32,33] which found out that risk of undernourishment increased along with increase in the age of a child. This is attributable to late introduction of supplementary food with low nutritional quality [34].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study found that age of the child significantly affected the child's nutritional status. This finding is consistent with findings from studies in Ethiopia and Bangladesh [23,26,32,33] which found out that risk of undernourishment increased along with increase in the age of a child. This is attributable to late introduction of supplementary food with low nutritional quality [34].…”
Section: Discussionsupporting
confidence: 92%
“…The study further indicated that among Ethiopian under-five children, males rather than females were more likely to be underweight, stunted or wasted. This result complies with findings from previous studies from Ethiopia and Burkina Faso [13,23,35]. A possible explanation is that childhood morbidity is higher among males rather than among females, even after adjusting for gestational age and body size [35].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A study conducted in Ghana showed that as the number of food groups consumed by mother increased, so too did the number consumed by their children (Amugsi, Mittelmark, & Oduro, ). Low socio‐economic status has been identified as a risk factor for low child dietary diversity in a wide range of contexts (Karwa, Godhia, & Jadhav, ; Rakotonirainy et al, ) and associations with stunted growth are well‐established (Adekanmbi, Kayode, & Uthman, ; Devakumar et al, ; Leroy, Habicht, Gonzalez de Cossio, & Ruel, ; Poda, Hsu, & Chao, ). Similarly, land ownership was also an important protective factor for child feeding practices in this study and others (Devakumar et al, ; Hailemariam, Girmay, & Girmay, ), perhaps due to the central role of agriculture in ensuring food security via food provision and/or income.…”
Section: Discussionmentioning
confidence: 99%
“…Children malnutrition status is highly correlated with their recent experience with the occurrence of diarrhoea and ARI related diseases. Evidence from several child malnutrition studies [28,29] suggest that the children recently suffered from diarrhoea and ARI are more likely to be either wasted (indicator of acute malnutrition) or underweight (combination of acute and chronic malnutrition). The national target of reducing wasting at 5% by 2025 [30] will be achievable if the prevalence of ARI and diarrhoea can be reduced as well.…”
Section: Discussionmentioning
confidence: 99%